Perspective of Faculty Members Regarding the Use of Logbook to Improve the Quality of Dental Education - Davoud Jamshidi; Fatemeh Sefidi; Sahar Ajiliyan; Kazem Hosseinzadeh (Mashhad University of Medical Sciences, 2023)
Background: This study aimed to assess the faculty members' perspective on the use of logbook to improve the quality of dental students' education. Method: This descriptive analytical study assessed the perspectives of all faculty members of Qazvin Dental School about using logbook in 2019. A questionnaire with four domains: 1) necessity of using a logbook (score range: 7-21), 2) format design and logbook implementation process (score range: 8-24), 3) logbook content quality (score range: 20-60), and 4) method of completion of logbook (score range: 2-10) was used to assess. The internal consistency of the items was assessed using Cronbach's alpha method (alpha-Cronbach: 0.81). Data were analyzed using SPSS 21 (p<0.05). Results: Of the faculty members, 19.4% were males and 80.6% were females, with a mean work experience of 6.81±5.3 years. The acquired mean total score was 18.72±2.57 out of 21 for the necessity domain, 15.33±2.78 out of 24 for the format design domain, 46.66±7.77 out of 60 for the content domain, and 8.00±1.43 out of 10 for the completion domain. Gender had a significant correlation only with the necessity domain score (P<0.05). Work experience had a significant correlation only with the completion domain score (P<0.05). Conclusion: Over two-thirds of the faculty members agreed with the necessity of using a logbook and believed that its completion is highly important.